Kompetensi Perawat dalam Merawat Pasien Gangguan Jiwa - Ah Yusuf; Rizki Fitryasari; Hanik Endang Nihayati; Rr. Dian Tristiana (Jurnal Ners, 2016)
Introduction: Competences of the nurse can be a good ability when supported with a positive perception of nurses about the competence itself. This study describe the nurse competencies in taking care patients with mental disorders and barriers in the implementation of these competencies. Methods: This study design used qualitative descriptive phenomenology. Population was nurse who worked at the Mental Hospital. Participants were 17 nurses from two  Mental Hospital in East Java which obtained by purposive sampling. Data was collected by indepth interview and focus group discussion (FGD).Equipment tools used media player, FGD guidelines and field notes. The data were analyzed by thematically analysis based Colaizzi. Result: The results produce eight themes. The nurse's perception of competence in caring for patients with mental disorders are implementing nursing care, Standard Procedures Operational (SPO) and nursing modality therapy. While nurses encounter obstacles when applying competence in the implementation of nursing documentation, limited facilities, the lack of effectiveness management system, limited human resource and the condition of the patient.  Discussion: The findings of this study can be used by nurses as a material to develop documentation formats more effectively and hospital management are expected to pay more attention to aspects of the guidance and supervision of the implementation of competence. Research suggested based on the findings is to analyze the relationship between supervision and nurse’s performance and satisfaction.